Molecular and Cellular Responses to Ionization Radiation in Untransformed Fibroblasts from the Rothmund–Thomson Syndrome: Influence of the Nucleo-Shuttling of the ATM Protein Kinase - Joëlle Al-Choboq; Myriam Nehal; Laurène Sonzogni; Adeline Granzotto; Laura El Nachef; Juliette Restier-Verlet; Mira Maalouf; Elise Berthel; Bernard Aral; Nadège Corradini; Michel Bourguignon; Nicolas Foray (Radiation, 2023)
The Rothmund–Thomson syndrome (RTS) is a rare autosomal recessive disease associated with poikiloderma, telangiectasias, sun-sensitive rash, hair growth problems, juvenile cataracts and, for a subset of some RTS patients, a high risk of cancer, especially osteosarcoma. Most of the RTS cases are caused by biallelic mutations of the RECQL4 gene, coding for the RECQL4 DNA helicase that belongs to the RecQ family. Cellular and post-radiotherapy radiosensitivity was reported in RTS cells and patients since the 1980s. However, the molecular basis of this particular phenotype has not been documented to reliably link the biological and clinical responses to the ionizing radiation (IR) of cells from RTS patients. The aim of this study was therefore to document the specificities of the radiosensitivity associated with RTS by examining the radiation-induced nucleo-shuttling of ATM (RIANS) and the recognition and repair of the DNA double-strand breaks (DSB) in three skin fibroblasts cell lines derived from RTS patients and two derived from RTS patients’ parents. The results showed that the RTS fibroblasts tested were associated with moderate but significant radiosensitivity, a high yield of micronuclei, and impaired DSB recognition but normal DSB repair at 24 h likely caused by a delayed RIANS, supported by the sequestration of ATM by some RTS proteins overexpressed in the cytoplasm. To our knowledge, this report is the first radiobiological characterization of cells from RTS patients at both molecular and cellular scales.